Obelix vs. Asterix: Size of US commercial banks and its regulatory challenge (2015)
Big banks pose substantial costs to society in the form of increased systemic risk and government bailouts during crises. So the question is: Should regulators limit the size of banks? To answer this question, regulators need to assess the potential costs of such regulations. If big banks enjoy substantial scale economies (i.e., average costs get lower as bank size increases), limiting the size of banks through regulations may be inefficient and likely to reduce social welfare. However, the literature offers conflicting results regarding the existence of economies of scale for the biggest US banks. We contribute to this literature using a novel approach to estimating nonparametric measures of scale economies and total factor productivity (TFP) growth. For US commercial banks, we find that around 73 % of the top one hundred banks, 98 % of medium and small banks, and seven of the top ten biggest banks by asset size exhibit substantial economies of scale. Likewise, we find that scale economies contribute positively and significantly to their TFP growth. The existence of substantial scale economies raises an important challenge for regulators to pursue size limit regulations.